Nicotine addiction is the main risk factor for the formation and development of chronic obstructive pulmonary disease: A review - Anna V. Dzyubailo; Viacheslav S. Lotkov (Consilium Medicum)
The article considers the issue of studying the effect of nicotine dependence on the development of chronic obstructive pulmonary disease, as the main factor in the formation of inflammation mediated through the use of tobacco-containing, as well as alternative tobacco products, not only the epithelium of the bronchi, but also the endothelial cells of large and small vessels. Morphological changes in bronchopulmonary structures lead to pronounced tissue hypoxia, which in turn aggravates the course of the underlying disease, leads to the formation of concomitant pathology in the form of cardiovascular diseases, pathology of blood rheology, increased risks of thrombosis. Without considering the risks of early death in this context, we can say with confidence that a decrease in the level of quality of life and human activity will directly depend on the availability of constant and prolonged use of nicotine-containing products.